The Island Topos: From Paradise to Prison (American & British Studies Annual, 2017)
This article deals with the transformation of the island topos. The island is frequently depicted as a paradise and prison in English literature and the article elaborates on the transformation of the two topoi. Prior to the depiction of the transformation, the article deals with perceptions and attitudes people have associated with islands throughout history. The core part of the article describes the process of the island transformation. It also points out the significant geographical features of islands which help to change the perception of the environment. Works by English authors such as, The Magus, Utopia, Web, Robinson Crusoe and Gulliver’s Travels are used in order to help illustrate the processes of this transformation.
Keywords: island; poetics of place; topos; John Wyndham